NGHIÊN CỨU CHẾ TẠO VÀ ĐÁNH GIÁ HIỆU LỰC CỦA KHÁNG THỂ IgY KHÁNG VI KHUẨN TẢ VÀ ĐỘC TỐ TẢ TRÊN THỰC NGHIỆM - Hoàng, Trung Kiên; Hoàng, Đức Hậu; Nguyễn, Đặng Dũng (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
RESEARCH ON PRODUCTION AND PROTECTIVE EFFECT OF YOLK IMMUNOGLOBULIN AGAINST VIBRIO CHOLERAE AND CHOLERATOXIN ON EXPERIMENTAL ANIMAL Cholera, an acute infectious disease caused by the Vibrio cholerae, which usually develops rapidly. Egg yolk immunoglobulin (IgY) used to treat and prevent cholera. In this study, IgY antibodies against V. cholerae and choleratoxin were created by immunization method for egg-laying hens. The eggs of immunizated hens were collected for isolating antibodies against V. cholerae and choleratoxin from yolk. These IgY antibodies had shown activity after purification, the V. cholera and choleratoxin specific IgY antibody had a specific response to antigen at 1/64,000 dilution and 1/200,000 dilution, respectively. In addition, the protective activity of antibodies was also carried out on animal model as V. cholera (1x108 CFU) and choleratoxin (1 mg/ml) injected mice. Subsequently, IgY antibody protected mice against V. cholerae as well as choleratoxin.